2021
DOI: 10.1007/s10916-020-01703-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic and the Importance of Telemedicine in Managing Acute ST Segment Elevation Myocardial Infarction Patients: Preliminary Experience and Literature Review

Abstract: The coronavirus disease 2019 , which is caused by a novel coronavirus (SARS-COV-2), has compromised health care systems and normal management of patients with cardiovascular diseases [1][2][3]. Patients with non-communicable diseases, including acute myocardial infarction (AMI) are vulnerable to this stress [4,5]. Acute ST segment elevation myocardial infarction (STEMI), the most critical type of AMI, is associated with high mortality even with modern medicine [6][7][8]. Timely reperfusion therapy is critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 74 publications
0
16
0
5
Order By: Relevance
“…Telemedicine has a potentially broad application to cardiovascular disease (CVD), and it might have an important role as part of a strategy for the delivery of effective healthcare for patients with CVD, especially those with MI that is considered a leading cause of mortality and morbidity ( 7 ). Many studies showed that telemedicine is widely used in the cardiovascular field, such as in remote blood pressure (BP) monitoring ( 8 ), pre-hospital electrocardiography in the management of MI ( 9 ), monitoring of arrhythmias ( 7 ), monitoring of anticoagulant therapy ( 10 ), and regular follow-up of chronic cardiac conditions such as in heart failure and following MI or PCI, especially following the coronavirus disease 19 (COVID-19) pandemic ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine has a potentially broad application to cardiovascular disease (CVD), and it might have an important role as part of a strategy for the delivery of effective healthcare for patients with CVD, especially those with MI that is considered a leading cause of mortality and morbidity ( 7 ). Many studies showed that telemedicine is widely used in the cardiovascular field, such as in remote blood pressure (BP) monitoring ( 8 ), pre-hospital electrocardiography in the management of MI ( 9 ), monitoring of arrhythmias ( 7 ), monitoring of anticoagulant therapy ( 10 ), and regular follow-up of chronic cardiac conditions such as in heart failure and following MI or PCI, especially following the coronavirus disease 19 (COVID-19) pandemic ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Management of patients with ST-segment elevation myocardial infarction (STEMI) amid COVID-19 was controversial at first, with some advocating for fibrinolytics to mitigate delays and protect healthcare workers 9 . However, it was soon realized that some of these patients have no culprit vessel on angiography, and it was found that this treatment strategy increased mortality 10 . Given these concerning findings, guidelines reinforced primary PCI as the standard of care for STEMI and non-ST-elevation myocardial infarction (NSTEMI) in patients with high-risk features 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine is also used to evaluate the diagnosis and treatment of patients after discharge when social distancing is required. As a result, the admission rate in hospitals decreases (Nan et al 2021 ). Critical diagnostic and monitoring of remote patients are other aspects of telemedicine that involve smartphone, Bluetooth, and global positioning system technologies.…”
Section: Discussionmentioning
confidence: 99%